Thyroid function in type 2 diabetes mellitus - Afrin, Sajeda; Sarkar, Chandra Rani; Zahid, ATM Zoadur Rahim; Ahmed, Neaz (Journal of Bangladesh Society of Physiologist, 2018)
Background: Type 2 Diabetes Mellitus (T2DM) and thyroid disorder are common endocrine disorders that affect major population worldwide. Subclinical hypothyroidism is common among T2DM. Objectives: To observe thyroid stimulating hormone (TSH), total thyroxine (TT4), free thyroxine (FT4), total triiodothyronine (TT3), free triiodothyronine (FT3) levels in newly diagnosed T2DM. Methods: This cross sectional study was conducted from July 2014 to June 2015. For this, 50 newly diagnosed T2DM patients aged 30 to 50 years of both sexes were enrolled from the Out Patient Department of Endocrinology, Rangpur Medical College and Diabetic Association, Rangpur. Fifty age matched non-diabetic healthy subjects of both sexes constituted control. Serum TSH, TT4 , FT4, TT3, FT3 levels were estimated to observe thyroid function. All these hormones were estimated by ELISA method. For statistical analysis independent sample “t” test was performed. Results: Serum TSH was significantly higher (p<0.001) and serum TT4, FT4, FT3 levels were significantly lower (p<0.001) in T2DM compared to control. Eight (16%) of T2DM were hypothyroid. Conclusion: From this study it can be concluded that altered thyroid status leading to hypothyroidism may be associated with T2DM. Bangladesh Soc Physiol. 2017, December; 12(2): 61-64